Constructing biocompatible carboxylic curdlan-coated zein nanoparticles for curcumin encapsulation. (November 2020) - Yu, Yun-Bo; Wu, Ming-Yu; Wang, Chun; Wang, Zi-Wei; Chen, Ting-Ting; Yan, Jing-Kun
Abstract: In this study, carboxylic curdlans with different carboxylate contents, molecular weights (MWs), and chain conformations (Cur-8, Cur-24, and Cur-48) were developed as hydrophilic coatings for hydrophobic zein nanoparticles (ZNPs) to encapsulate curcumin. The results showed that the freshly prepared curcumin-loaded ZNPs (ZC) had spherical structures, a particle size of ~183.0 nm, a zeta potential of +17.7 mV, and an encapsulation efficiency of 66.7%. The anionic carboxylic curdlan coating on the surface of ZC affected the particulate and physicochemical characteristics of the encapsulated curcumin and effectively improved its water dispersibility, photo- and thermostability, and sustained release behavior in aqueous environments. These properties were correlated with the carboxylate content, MW, and chain conformation of the carboxylic curdlans. The observed improvements were attributed to hydrogen bonding, hydrophobic and electrostatic interactions among curcumin, ZNPs, and carboxylic curdlans. The curcumin encapsulated in the Cur-24-coated ZNPs exhibited stronger antioxidant capacity in vitro than the other samples. Therefore, carboxylic curdlan-coated ZNPs have considerable potential for use in hydrophobic nutraceutical encapsulation. Graphical abstract: Carboxylic curdlans with different molecular properties and chain conformations could serve as hydrophilic coatings of hydrophobic zein nanoparticles encapsulating curcumin and resulted in enhanced water dispersibility, photo- and thermo-stability, controlled release ability, and antioxidant activity in vitro. Image 1 Highlights: Carboxylic curdlan (CC)-coated zein nanoparticles were used to encapsulate curcumin. Molecular properties and conformations of CC affected the encapsulation of curcumin. Coating enhanced physicochemical and delivery properties of the entrapped curcumin. Hydrogen bonds, hydrophobic and electrostatic interactions were main driving forces. CC-coated zein nanoparticles served as desirable vectors for hydrophobic nutrients.